Methodology in Visual Poetics - Peled, Yiftah (PORTO ARTE: Revista de Artes Visuais, 2013)
The insertion of artists in the research in Visual Poetics in different Visual Arts postgraduate programs promotes a process of blending of these agents’ role. The combination of artist and researcher presents a need to build adequate methodologies to the objectives of this study field. To this construction were used different elements: the fundamental work of Marcel Duchamp, the concept of performance and the critical discussion on the theme and thesis and dissertations done by artists/authors who proposed inciting methodologies in post-graduation in the visual poetics’ field.